RESPON PRODUKSI KELAPA SAWIT DALAM PANENTUAN DOSIS OPTIMUM UREA DAN MOP PADA TANAH TYPIC PALEUDULT - Bukti Hasiholan (JURNAL AGROTEKNOSAINS, 2019)
Determination of the optimum dosage of urea fertilizer (source N) and MOP (source K) in oil palm producing (TM) plants through fertilization experiments in the field is very important because the plant needs for both types of fertilizers are relatively high. N-K fertilization trials on TM (aged 4-12 years) have been conducted at one location of PT.Salim Ivomas Pratama Tbk & Subs (in two gardens: Lubuk Raja Estate and / Balam Rumbia Estate) during the 1992-2000 time period. The urea and MOP fertilization treatments separately showed the response of FFB production by 22 and 50%, respectively (1995 - 2000). The interaction of urea and MOP is not real. The response curve of FFB production to urea and MOP doses showed that the optimum dosage in Typic Paleudult soil types for TM aged 7-12 years was 2.50 kg urea and 3.00 kg MOP / tree / year to achieve the production target of 28 tons of FFB / ha /year.To get the maximum fertilizing effect, fertilization must be done by using the type of fertilizer, the correct method and time of fertilization, and with fertilizer quality that is in accordance with specifications (for example SNI or Indonesian National Standard). An examination of the quality of fertilizers is important so that the company avoids multiple losses that have a large impact on production.